Middle Manager Leadership Behavior of Government Officials in Indonesia - BASUKI, Johanes (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020DO - 10.14505/jarle.v11.2(48).04, 2020)
Changes in the leadership behavior of the middle managers in the ranks of government bureaucracy, including: insight, decision making, ability to influence others, the use of authority, and ability in interpersonal relationships, can be performed by increasing the educational value, leadership training, functional techniques as well as empowerment and development in the workplace. The empowerment and development includes\ improving organizational commitment such as: partiality attitude, working engagement, performance improvement, conflict control, a sense of commitment, obedience, and loyalty to the organization where a middle manager is in charge; and decreasing the sense of boundaries; setting clear and unambiguous standard of performance results and, equity in awarding activity, clear goals of the organization, warmth and support in the working relationship, and the risk-taking.